Deploying of Animatic in TV Drama: محمد ثائر البياتي (Al-Academy, 2016)
This research laid the recruitment & use of IT Animatic digital TV drama & inviting ways of working is simple &effective in the level of producing images especially in TV drama, so the entry of this technology has created the concepts of new technology, and simple & effective at the same time with high level of modernity & technical innovation, this research deals with three chapters that includes two topics the animatic modes & the stages of production , & what is the atheistic aspects that is provided by this technology with the researcher reviewing the use of some TV dramatic Production series that was mentioned through this research.Which afterwards the researcher has analyzed a sample that was selected for a mentioned reason basically for it was produced by animatic digital technology m than the researcher concluded results & made a conclusion that this awesome research has obtained through its work, & finally there is an appendix in the end line of this research that shows images of the analyzed sample data